Idiotype vaccines for lymphoma: Potential factors predicting the induction of immune responses - Inoges, Susana (Baishideng Publishing Group Co., Limited, 2011)
Over the last two decades, lymphoma idiotype vaccines have been the first human cancer vaccines to show striking evidence of biological and clinical efficacy on the one hand, as well as clinical benefit on the other. More recently, however, three large-scale, independent, randomized clinical trials on idiotypic vaccination have failed to achieve their main clinical endpoints for reasons likely to depend more on flaws in each clinical trial’s study design than on each vaccination strategy per se. Independently of these considerations, a major hurdle for the development of this substantially innocuous and yet potentially very effective type of treatment has been the fact that, even to date, no factors ascertainable before vaccination have been prospectively singled out as predictors of subsequently vaccine-induced, idiotype-specific immune as well as clinical responses. The aim of this review article is precisely to analyze what has been and what could be done in this respect in order to give a greater chance of success to future trials aimed at regulatory approval of idiotype vaccines.